Proliferative vitreoretinopathy and its relationship with inflammatory serum biomarkers - Victor Alejandro Martinez Pacheco; Sergio Rojas Juarez; Braulio Hernan Velasco Sepulveda; Abel Ramirez Estudillo (International Journal of Ophthalmology, 2024)
AIM: To analyze if a relationship between levels of inflammatory serum biomarkers and severity of primary proliferative vitreoretinopathy (PVR) exists. METHODS: A retrospective case-control study. The healthy adult patients with rhegmatogenous retinal detachment and primary PVR were included in the PVR group. For the control group, healthy adults who underwent cataract surgery were included. The grade of PVR was classified according to the Retinal Society Terminology Committee. Blood samples were obtained before surgery, and processed in MYTHIC 18. Measures of interest were neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR), the time between the decrease in visual acuity and surgery, PVR grade, type of surgery, final best corrected visual acuity, and rate of re-detachment. RESULTS: Totally 240 patients were included, 120 in each group, 79 (65.8%) and 56 (46.7%) were male in the PVR and control group, respectively. PVR A had greater levels of monocytes (0.28±0.18 vs 0.12±0.32, P=0.002), neutrophils (4.59±1.51 vs 3.92±1.27, P=0.006), and LMR (9.32±4.42 vs 7.43±3.90, P=0.01). PVR B had a greater monocyte count (0.30±0.13 vs 0.12±0.32, P=0.001), and PVR C demonstrated higher levels in monocytes (0.27±0.12 vs 0.12±0.32, P=0.004), neutrophils (4.39±1.13 vs 3.92±1.27, P=0.004), and LMR (9.63±3.24 vs 7.43±3.90, P=0.002) compared to control, respectively. An LMR cut-off value of 9.38 predicted PVR with a sensibility of 54.2% and specificity of 77.5% and NLR cut-off of 1.70 predicted PVR with a sensibility of 62% and specificity of 54.2%. CONCLUSION: Patients with primary PVR demonstrate greater neutrophil, monocyte, and LMR levels than the control group. Cut-off values obtained from ratios could be useful in a clinical setting when no posterior view of the fundus is possible due to media opacity.